The Potential Role of Major Argan Oil Compounds as Nrf2 Regulators and Their Antioxidant Effects - Riad El Kebbaj; Habiba Bouchab; Mounia Tahri-Joutey; Soufiane Rabbaa; Youness Limami; Boubker Nasser; Melford C. Egbujor; Paolo Tucci; Pierre Andreoletti; Luciano Saso; Mustapha Cherkaoui-Malki (Antioxidants, 2024)
In recent years, research on the discovery of natural compounds with potent antioxidant properties has resulted in growing interest in these compounds due to their potential therapeutic applications in oxidative-stress-related diseases. Argan oil, derived from the kernels of a native tree from Morocco, Argania spinosa, is renowned for its rich composition of bioactive compounds, prominently tocopherols, polyphenols, and fatty acids. Interestingly, a large body of data has shown that several components of argan oil activate the nuclear factor erythroid 2-related factor 2 (Nrf2) pathway, playing a crucial role in the cellular defense against oxidative stress. Activation of this Nrf2 pathway by argan oil components leads to the increased expression of downstream target proteins like NAD(P)H quinone oxidoreductase (NQO1), superoxide dismutase (SOD), heme oxygenase 1 (HO-1), and catalase (CAT). Such Nrf2 activation accounts for several health benefits related to antioxidant defense, anti-inflammatory effects, cardiovascular health, and neuroprotection in organisms. Furthermore, the synergistic action of the bioactive compounds in argan oil enhances the Nrf2 pathway. Accordingly, the modulation of the Kelch-like ECH associated protein 1 (Keap1)/Nrf2 signaling pathway by these components highlights the potential of argan oil in protecting cells from oxidative stress and underlines its relevance in dietetic prevention and therapeutic applications. This review aims to provide an overview of how major compounds in argan oil activate the Nrf2 pathway, updating our knowledge on their mechanisms of action and associated health benefits.